Analisis kinerja terkait kepuasan masyarakat layanan teman bus (Studi kasus: Angkutan Umum Koridor 2) - Setiawan, Agung; Said, Lambang Basri; Syafei, Ilham (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Public transportation constitutes a service designed for the conveyance of passengers, characterized by a collective travel framework accessible to the broader populace. The rise in population leads to an escalation in human mobility, thereby amplifying the demand for transportation services. In alignment with the problem formulation, the objective of this study is to 1) Examine the factors that affect the degree of user satisfaction regarding the performance of Teman Bus transportation services along Corridor II Panakkukang Square - Sultan Hasanuddin International Airport in Makassar City. 2) investigate the primary factors that significantly impact user satisfaction regarding Teman Bus transportation services along Corridor II from Panakkukang Square to Sultan Hasanuddin International Airport in Makassar City. The research method is descriptive qualitative analysis with SPSS Version 21. The results obtained are as follows. Regression Equation Model: Y = 15.160 + 0.457X1 + 0.255X2 - 0.011X3 + 0.686X4 - 0.1547X5 - 0.42X6 + 0.254X7 Using the following description: Variable: X1 Physical Aspect of Infrastructure has a coefficient value of 0.457. Variables: X2 Reliability Aspect, coefficient value 0.255; X3 Responsiveness Aspect, coefficient value 0.011. Variable: X4 Security Assurance Aspect, having a coefficient value of 0.686. Variables: X5 Empathy Aspect (0.1547), X6 Accessibility Aspect (0.422), and Variable: X7 Comfort Aspect has a coefficient value of 0.254.